2012
DOI: 10.1039/c1cp22965f
|View full text |Cite
|
Sign up to set email alerts
|

Structure and function of proteins in hydrated choline dihydrogen phosphate ionic liquid

Abstract: Ionic liquids are being intensely studied as promising media for the stabilization of proteins and other biomolecules. Choline dihydrogen phosphate (CDHP) has been identified as one of the most promising candidates for this application. In this work we have probed in more detail the effects that CDHP may have on the thermodynamics, structure, and stability of proteins, including one of therapeutic interest. Microcalorimetry and circular dichroism spectropolarimetry (CD) were used to assess the thermal stabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
75
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(77 citation statements)
references
References 39 publications
(57 reference statements)
2
75
0
Order By: Relevance
“…Their application as media for maintaining the protein stability has been extensively studied, either employed as co-solvents with water, in biphasic systems, or as "neat" solvents [8][9][10][11]. Some reports also demonstrated that some ILs are able to maintain or even increase the proteins stability [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Their application as media for maintaining the protein stability has been extensively studied, either employed as co-solvents with water, in biphasic systems, or as "neat" solvents [8][9][10][11]. Some reports also demonstrated that some ILs are able to maintain or even increase the proteins stability [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…9 Using measurements of far-UV circular dichroism spectropolarimetry at 222nm, we observed an increase in thermal midpoint of unfolding temperature (T m ) of recombinant human IL-2 (rhIL-2) in the presence of CDHP. However, the effects on rhIL-2 bioactivity were not explored.…”
Section: Resultsmentioning
confidence: 99%
“…The reported T m values are included here as follows: (1) 30mM NaH 2 PO 4 : T m = 61.7°C, (2) 30mM CDHP pH 7.4: T m =60.2°C, (3) 185mM CDHP pH 7.4: T m =63.0°C, and (4) 680mM CDHP pH 7.4: T m = 74.2°C. 9 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indirect Fourier Transformation (IFT) Analysis is a method that has been applied in studies of protein stability in a hydrated choline di-hydrogen phosphate ionic liquid [32]. The IFT analysis can also be useful in identifying unknown phases, as well as understanding the link between real space and reciprocal space.…”
Section: Indirect Fourier Transformation Analysismentioning
confidence: 99%